Membrane technology and applications - Baker, Richard W. 1941- (Wiley, 2012)
"Building on the success of the previous edition, Membrane Technology and Applications Third Edition provides a comprehensive overview of separation membranes, their manufacture and their applications. Beginning with a series of general chapters on membrane preparation, transport theory and concentration polarization, the book then surveys several major areas of membrane application in separate chapters. Written in a readily accessible style, each chapter covers its membrane subject thoroughly, from historical and theoretical backgrounds through to current and potential applications. Topics include reverse osmosis, ultrafiltration, pervaporation, microfiltration, gas separation and coupled and facilitated transport; chapters on electrodialysis and medical applications round out the coverage."--Resumé vydavatele
Předchozí vydání: 2004
Keywords: membrány; technické membrány; membránový transport; membránové procesy; membranes; technical membranes; membrane transport; membrane processes; elektronické knihy; electronic books